Trading as a business : the methods and rules I've used to beat the markets for 40 years - Diamond, Dick (Stockbroker) (Hoboken, New Jersey : Wiley, 2015)
"Discover what legendary trader Dick Diamond knows about trading that you don'tTrading as a Business: The Methods and Rules I've Used To Beat the Markets for 40 Years gives you a behind-the-scenes look at how Dick Diamond has become a successful independent trader for more than four decades. This vital resource reveals Diamond's methods for analyzing the market and knowing the right time to get in and out of trades. With this book in hand, you'll be able to tap into Diamond's strategy of 80/20 trading which offers an 80% chance of making a winning trade. Diamond also includes his six statistics that are critical for determining where the stock market is headed. This book is written for anyone who wants to learn the methods, tools, and techniques that will transform them from an ordinary investor into a trading force in the marketplace. Once you master the trading secrets from Dick Diamond, you will have the ability to make money in a business where you call the shots. Filled with Dick Diamond's trading secrets for beating the market Includes a wealth of trader strategies including Diamond's 80/20 technique Discover how to identify and take advantage of the market's buy and sell zones Learn what it takes to become an independent trader who makes money over the long-haul Break free of your old trading habits and discover Dick Diamond's tools and techniques for financial freedom"--
Chapter 7 Trading with the Bressert TemplateChapter 8 Trading with the RMO Template; Chapter 9 A Day of Trading; Appendix: About MetaStock Pro Templates; Creating the Dick Diamond Templates; Template 1: Walter Bressert; Template 2: Moving Ribbons; Template 3: RMO; Template 4: Moving Averages; Applying an Existing Template; Making Changes to a Template; Saving a Template; The Default Template; Creating the Diamond Work Space; About the Author; Index; EULA.
Includes index.
Print version record and CIP data provided by publisher.
Keywords: Investment analysis; Speculation; Investments; Portfolio management; Stockbrokers; Investment analysis; Investments; Portfolio management; Speculation; Stockbrokers; BUSINESS & ECONOMICS -- Finance; Investment analysis; Investments; Portfolio management; Speculation; Stockbrokers; Electronic books